1941
DOI: 10.1021/j150410a002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrolytes in Hydrophobic Systems. I. Electric Mobility and Stability.

Abstract: 1. The critical mobilities of several monovalent ions of different co" agulating power have been determined for colloidal manganese dioxide.2. These values were found to be higher the lower the coagulating power EFFECTS OF ELECTROLYTES IN HYDROPHOBIC SYSTEMS. II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1941
1941
1951
1951

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In the Aerosol solution, where a much greater degree of dispersion is postulated, this second factor becomes inconsequential. The greater sedimentation volume found with the more acid water is probably attributable to an increase in aggregation resulting from lowering of the zeta potential by adsorption of hydrogen ion, since manganese dioxide is known to be negatively charged in aqueous dispersion (16,36).…”
Section: Sedimentation Volumesmentioning
confidence: 99%
“…In the Aerosol solution, where a much greater degree of dispersion is postulated, this second factor becomes inconsequential. The greater sedimentation volume found with the more acid water is probably attributable to an increase in aggregation resulting from lowering of the zeta potential by adsorption of hydrogen ion, since manganese dioxide is known to be negatively charged in aqueous dispersion (16,36).…”
Section: Sedimentation Volumesmentioning
confidence: 99%
“…As opposed to the characteristics which are associated with the coagulation of a sol of a given concentration with a strongly adsorbable polyvalent ion, the phenomena associated with the flocculation of the same sol by an electrolyte of the potassium chloride type are as follows: (1) a high concentration of electrolyte is required; and (2) coagulation occurs at a high critical mobility. These phenomena have been discussed in a previous communication (5), where it was proposed that compression of the electric double layer at high electrolyte concentrations played an important róle in the precipitation of sols with univalent ions of low adsorbability.…”
Section: Resultsmentioning
confidence: 85%
“…The effects of electrolytes on the mobility and the stability of a manganese dioxide sol and of an arsenic trisulfide sol of different concentrations were studied in the present investigation. The same stock samples of sols were used in this work as were employed in the critical mobility studies previously reported (5), and, in both cases, the experimental techniques were the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous communication (2) an explanation was offered to account for the high critical mobilities toward certain poorly adsorbable monovalent ions. It was concluded that compression of the double layer at high electrolyte concentrations was of primary importance in the coagulation of sols by ions of this valence type.…”
Section: Discussionmentioning
confidence: 99%